An integrated ecosystem model for understanding infrastructure PPPs. (October 2016) - Leviäkangas, Pekka; Ojala, Lauri; Töyli, Juuso
Abstract: To overcome the seemingly chronic funding gap for public infrastructure investments, well over thousand Public-Private Partnerships (PPPs) have been carried out around the world with varying success in terms of investor returns and socio-economic sustainability. This paper proposes an integrated model that assesses PPP projects at three levels of observation: i) the market; ii) the cash-flow of a project; and iii) the ecosystem around PPPs. The aim is to build a more holistic yet comprehensible framework that links these three levels to better understand PPPs especially in the context of infrastructure projects. It can also be modified to fit multiple contexts and used as a tool for analysing PPPs in their early stages. Highlights: Cash flow and cost-benefit modelling are combined for PPP appraisal. The result is an integrated appraisal model that is particularly useful in the early stages of PPP project appraisal. The integrated model shows the financial transactions and economic flows within the ecosystem of a PPP and in different market layers. The model suggests that PPP policies and strategies should focus also on entire market layers.